2007
DOI: 10.1097/01.rli.0000261935.41188.39
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Tensor Imaging at 3 T

Abstract: FAIs based on mean fractional anisotropy values obtained from isotropic whole-head high-field diffusion tensor imaging by fully automated algorithms represent a robust and observer-independent measure for the comparative assessment of white matter integrity, ideally suited for further statistical treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…However, several studies have reported no correlations between clinical information and structural measures from T1-weighted MRI in patients with TLEhs [6], [19], [66], [67]. It may be expected that associations between regional brain architecture and clinical variables would be more revealing using DTI, given the increased sensitivity of DTI over conventional MRI in the detection of pathological brain alterations [7], [38], which is supported by the findings presented in this paper. In particular, we found evidence of widespread regional FA-duration of epilepsy correlations, including the necessary correction for age, but only one volumetric-duration correlation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, several studies have reported no correlations between clinical information and structural measures from T1-weighted MRI in patients with TLEhs [6], [19], [66], [67]. It may be expected that associations between regional brain architecture and clinical variables would be more revealing using DTI, given the increased sensitivity of DTI over conventional MRI in the detection of pathological brain alterations [7], [38], which is supported by the findings presented in this paper. In particular, we found evidence of widespread regional FA-duration of epilepsy correlations, including the necessary correction for age, but only one volumetric-duration correlation.…”
Section: Discussionsupporting
confidence: 81%
“…Given that axonal membranes play the primary role for significant anisotropy in DTI data [38], the study of FA has largely been limited to that of white matter. Furthermore, noise in DTI data can bias the calculated diffusion tensor and lead to an overestimate of diffusion anisotropy when the signal-to-noise ratio and actual anisotropy are low [39], [40], which may potentially overwhelm FA in areas with relatively low diffusion anisotropy such as gray matter [41].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of WMHs in AD may reflect multiple physiological and pathological changes such as breakdown of the blood-brain barrier [20], impaired cerebral auto-regulation [21], vasculopathies, and inflammation [22, 23]. In healthy adults, homozygotes for the IL-1 beta -511 T allele have been associated with increased inflammatory responses and larger WMHs than the other two genotypic combinations [24].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, FA provides a measure of the degree to which a single direction of water motion dominates overall diffusivity in a voxel. As such, FA has been shown to be a relatively robust measure of white matter integrity (Lee et al, 2012; Beppu et al, 2012; Qiu et al, 2010; Ptak et al, 2003; Deppe et al, 2007). …”
Section: Introductionmentioning
confidence: 99%